Abietane diterpenoids from Salvia officinalis leaves as aryl hydrocarbon receptor ligands. (February 2021) - Nishino, Katsutoshi; Someya, Kenta; Ksouri, Riadh; Ishikawa, Toshio; Isoda, Hiroko; Irie, Kazuhiro; Nagao, Masaya
Graphical abstract: Highlights: One undescribed diterpenoid was isolated from Salvia officinalis leaves as an AhR ligand. The structure of the undescribed diterpenoid was determined by spectroscopic analyses. Seven diterpenoids exhibited ligand activity for the aryl hydrocarbon receptor. Abstract: One undescribed and six known abietane diterpenoids were isolated as ligands for aryl hydrocarbon receptor (AhR) from leaves of Salvia officinalis, a folk medicine in the Mediterranean Sea area. The structure of the undescribed diterpenoid named (+)-(10 R )-11, 14-dioxoabieta-8, 12-diene-12, 20-diol was assigned by 1D/2D NMR spectroscopic and HR-ESI-MS data. The AhR ligand activity of the isolated diterpenoids was evaluated by AhR-dependent luciferase reporter system stably transfected in HepG2 cells (HepG2-XRE). Each AhR ligand derived from Salvia officinalis exhibited AhR ligand activity at 30 μM.